2011
DOI: 10.1021/ol103149b
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Multicomponent Synthesis of Diversely Substituted 2-Aminopyrroles. A Short General Synthesis of Rigidins A, B, C, and D

Abstract: Privileged medicinal scaffolds based on the structures of tetra-and penta-substituted 2-aminopyrroles were prepared via one-pot multicomponent reactions of structurally diverse aldehydes and N-(aryl-, hetaryl-, alkyl-sulfonamido)-acetophenones with activated methylene compounds. This methodology was used in a four-step synthesis of alkaloids rigidins A, B, C and D in overall yields 61%, 58%, 60% and 53%, respectively. Of these, rigidins B, C and D were synthesized for the first time.Polysubstituted pyrroles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 62 publications
1
42
0
Order By: Relevance
“…To develop synthetic access to the C2-substituted 7-deazahypoxanthines D , a previously discovered 13 multicomponent reaction (MCR) of sulfonamidoacetophenones with aldehydes and cyanoacetamide was utilized to prepare pyrrole 1 (Table 1). This was followed by the pyrimidine ring closure using the reaction of 1 with a variety of aromatic and aliphatic esters catalyzed by sodium ethoxide in ethanol that was reported for a related purine system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To develop synthetic access to the C2-substituted 7-deazahypoxanthines D , a previously discovered 13 multicomponent reaction (MCR) of sulfonamidoacetophenones with aldehydes and cyanoacetamide was utilized to prepare pyrrole 1 (Table 1). This was followed by the pyrimidine ring closure using the reaction of 1 with a variety of aromatic and aliphatic esters catalyzed by sodium ethoxide in ethanol that was reported for a related purine system.…”
Section: Resultsmentioning
confidence: 99%
“…To a stirred solution of N- methylsulfonamidoacetophenone 13 (0.084 g, 0.4 mmol), benzaldehyde (0.055 g, 0.52 mmol) and cyanoacetamide (0.044 g, 0.52 mmol) in EtOH (3 mL) was added anhydrous granulated K 2 CO 3 (0.028 g, 0.2 mmol). The mixture was then refluxed for 14 h. After this time the reaction mixture was cooled to room temperature and concentrated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we showed that pentasubstituted pyrroles 11 can be prepared by reacting various sulfonamidoacetophenones 10 with aldehydes and active methylene compounds with the subsequent oxidation of the intermediate pyrrolines with DDQ [7]. In addition, if the mixture of these three components is treated with ethanolic K 2 CO 3 , the reaction proceeds via sulfonyl elimination and provides tetrasubstituted pyrroles 12 .…”
mentioning
confidence: 99%
“…We utilized the latter MCR in the synthesis of marine alkaloids rigidins A, B, C, and D, isolated from tunicates obtained near Okinawa and New Guinea [7]. To this end, commercially available aminoacetophenones 13 are converted to the corresponding sulfonamides, which are then condensed with the requisite aldehydes and cyanoacetamide in the presence of K 2 CO 3 to give tetrasubstituted pyrroles 14 .…”
mentioning
confidence: 99%